"June, 1993" - Julian Hawthorne (1846-1934) (The Cosmopolitan: a Monthly Illustrated Magazine, 1893)
Satire and eutopia. The satire focuses on the "sleeper awakes" form that was so popular at the time. The eutopia is based on advanced technology that allows people to live at a distance from their work. This results in everyone living on a plot of land of about ten acres, with the disappearance of most cities. Both industry and cultural institutions are grouped into eight locations, four and four, throughout the country.
Rpt. in Scientific Romance: An International Anthology of Pioneering Science Fiction. Ed. Brian M[ichael] Stableford (Mineola, NY: Dover Publications, 2017), 187-97.
Keywords: Male author; US author